India's development and public policy - Nagel, Stuart S (Ed.) (Aldershot Ashgate, 2000)
This book analyzes India`s development and public policy from the perspectives of five major fields of public policy.They consist economic policy including public policy towards industrial development;social policy,including religion,education amd women`s
Keywords: India-Economic policy-1947-; Economic development; Social planning-India; India-Politics and government-20th century